CHEWING GUM CAN OVERCAOME POST OPERATIVE ILEUS ON ABDOMINAL SURGERY PATIENTS : CASE STUDY JAYAPURA GENERAL HOSPITAL PAPUA" - Rohmani Rohmani; Hugo Kinsgon Borneo; Frengky Apay; Ardhanari H. Kusuma (International Journal Of Health Science, 2023)
Background: Postoperative ileus is a major and transient problem in patients undergoing abdominal operative. Postoperative ileus commonly occurs at 25% of patients undergoing abdominal surgery. Signs symptoms of postoperative ileus include abdominal distension, nausea, vomiting, inability to the oral diet both eating and drinking, absence of flatus, and changes in defecation (gastrointestinal motility). Due to the presence of ileus patients are at high risk of developing complications, expensive treatment costs, lengthy stay, and late oral administration to the diet According to guidelines for post-surgery in digestion as well as gynecology in guidline enhanced recovery after surgery community recommends the use of chewing gum (shame feeding) to prevented post-operative ileus or ileus post-surgery. So there are several types of interventions to reduce postoperative ileus, namely implementing chewing gum as an evidence-based practice aimed at improving intestinal motility and minimizing side effects of postoperative ileus. Chewing gum is inexpensive, easily available, and a non-pharmacological intervention capable of producing changes in gastrointestinal motility and rapidly reducing the ileus post-operative. Furthermore, chewing gum interventions are relatively easy for nurses to implement. Research purpose: Effect of chewing gum on postoperative ileus prevention in postoperative abdominal patients. Research Methods: This type of research is quantitative research with a pre- and post-control quasi-experimental approach with a total of 30 respondent. Sampling using the accidental sampling method because respondent in hospital Jayapura city for abdominal surgery are still limited. The examinations used were the Wilcoxon and Man Whitney tests. Results: For the univariate analysis, it was found that male respondents were 20 respondents (66.7%) and women were 10 respondents (33.3). The age of the most respondents was 16 - 35 years old as many as 19 respondents (63.3%) and the least between 56 - 75 years old as many as 2 respondents (6.7%). Wilcoxon test results obtained p-value of 0.001 < 0.005 its mean that there is The chewing gum on improved intestinal motility of patients after abdominal operative. summary: chewing gum on the decline of ileus postoperative.